Filter – Medienwissenschaftliche Symposien der DFG

Fast Convergence of Inertial Multiobjective Gradient-Like Systems with Asymptotic Vanishing Damping - Sonntag, Konstantin; Peitz, Sebastian (SIAM Journal on Optimization)
We present a new gradient-like dynamical system related to unconstrained convex smooth multiobjective optimization which involves inertial effects and asymptotic vanishing damping. To the best of our knowledge, this system is the first inertial gradient-like system for multiobjective optimization problems including asymptotic vanishing damping, expanding the ideas previously laid out in [H. Attouch and G. Garrigos, Multiobjective Optimization: An Inertial Dynamical Approach to Pareto Optima, preprint, arXiv:1506.02823, 2015]. We prove existence of solutions to this system in finite dimensions and further prove that its bounded solutions converge weakly to weakly Pareto optimal points. In addition, we obtain a convergence rate of order \(\mathcal{O}(t^{-2})\) for the function values measured with a merit function. This approach presents a good basis for the development of fast gradient methods for multiobjective optimization.
Keywords: multiobjective optimization; Pareto optimization; Lyapunov analysis; gradient-likedynamical systems; inertial dynamics; asymptotic vanishing damping; fast convergence

Digitales und prädiktives Kompetenzmanagement

Imagining and Governing Artificial Intelligence – the Ordoliberal Way: An Analysis of the National Strategy ‘AI Made in Germany’ - Hälterlein, Jens (AI & Society)

“Meaningful Human Control” and Complex Human-Machine Assemblages – On the Limits of Ethical AI Principles in the Context of Autonomous Weapons Systems - Hälterlein, Jens; Weber, Jutta (Ethics and Armed Forces)

Biometrische Gesichtserkennung – Technologischer Solutionismus für mehr „Sicherheit“ - Hälterlein, Jens (CILIP Bürgerrechte & Polizei)

Fähigkeitsprofile im Physikdidaktischen Wissen mithilfe von Machine Learning - Zeller, Jannis; Riese, Josef (Frühe naturwissenschaftliche Bildung, Tagungsband der GDCP Jahrestagung 2023)
Das Fachdidaktische Wissen (FDW) wird als zentrale Komponente des Professionswissens von Lehrkräften bereits lange intensiv untersucht. Bislang liegen Ergebnisse zu Zusammenhängen des FDW mit anderen Professionswissensbereichen, zur Performanz in prototypischen Handlungssituationen und erste datengestützte inhaltlich-hierarchische Analysen auf Basis von Item Response Modellen (IRT-Modellen) vor. Im Zusammenhang mit einem projektübergreifend durchgeführten Vergleich entsprechender IRT-Modelle haben sich jedoch Limitationen bei der Vereinbarkeit und der inhaltlichen Reichhaltigkeit entsprechender Ergebnisse gezeigt, wie im Beitrag vorgestellt wird . Daher werden Analysemethoden aus dem Bereich des Machine Learning (unsupervised) vorgeschlagen, welche im Gegensatz zu IRT-Modellen auch nicht-hierarchische inhaltliche Strukturen aufdecken können. Es werden Ergebnisse entsprechender Clusteranalysen sowie Analysepläne zur Unterstützung dieser auf Basis der authentischen Sprachproduktionen von Proband:innen mithilfe von Natural Language Processing vorgestellt.
Keywords: Physikdidaktisches Wissen; Fähigkeitsprofile; Machine Learning

Realizing Concurrency on Top of the Microkernel seL4 via Improved Threads - Delgado Steuter, Dominik

Time and Transformation in Autobiography: Candia McWilliam’s What to Look for in Winter: A Memoir in Blindness - Mildorf, Jarmila (Perspektywy Kultury / Perspectives on Culture)

On the Shape Containment Problem within the Amoebot Model with Reconfigurable Circuits - Artmann, Matthias

The Interplay of Sound Tapestry and Music in the 1992 German Radio Play Adaptation of J.R.R. Tolkien’s The Lord of the Rings - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama: An Introduction - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama

Das Unbehagen der Vermittler*innen – Was Grundschullehrer*innen über Holocaust-Bilderbücher für den Grundschulunterricht denken. Ergebnisse einer Interviewstudie zur Praxisakzeptanz literarästhetischer Holocaust-Begegnungen im Grundschulunterricht (Deutsch) - Kanning, Julian; Kruse, Iris; Inhoff, Julia (Deutschunterricht als Gedächtnisagentur. Didaktische Annäherungen an eine spezifische schulische Erinnerungskultur)

Analyzing student response processes to refine and validate a competency model and competency-based assessment task types - Soyka, Chantal; Schaper, Niclas (Frontiers in Education)

Bits und Bytes - Mikrocontroller verstehen mit modularer Hardware - Hetkämper, Tim; Meihost, Lars

Die (Ent-)Territorialisierung der Idylle. Zur produktiven Wechselseitigkeit surrealistischer Sehnsuchtsorte in bildender Kunst und Kinder- und Jugendmedien im Kontext der Studien visueller Kulturen - Böker, Ines (Idyllen und Sehnsuchtsorte in Literatur und Medien für Kinder und Jugendliche)

Evaluation and thermodynamic optimization of phase diagram of lithium niobate tantalate solid solutions - Bashir, Umar; Klimm, Detlef; Rüsing, Michael; Bickermann, Matthias; Ganschow, Steffen (Journal of Materials Science)
The lithium niobate–lithium tantalate solid solution’s phase diagram was investigated using experimental data from differential thermal analysis (DTA) and crystal growth. We used XRF analysis to determine the elemental composition of the crystals. The Neumann–Kopp rule provided essential data for the end members lithium niobate (LN) and lithium tantalate (LT). The heats of fusion of the end members, given by DTA measurements, are 103 kJ/mol at 1531 K for LN and 289 kJ/mol at 1913 K for LT. These values were used as input parameters to generate the data. This data served as the basis for calculating a phase diagram for LN-LT solid solutions. Finally, based on the experimental data and a thermodynamic solution model, the Calphad Factsage module optimized the phase diagram. We also generated thermodynamic parameters for Gibbs’ excess energy of the solid solution. A plot of the segregation coefficient as a function of Ta concentration was derived from the phase diagram.

Digitalisierungsbezogene Kompetenzen (angehender) Chemielehrkräfte - Ponath, Jonas; Bohrmann-Linde, Claudia; Rubner, Isabel; Sommer, Katrin; Fechner, Sabine (Frühe naturwissenschaftliche Bildung)

Ein Beitrag zur Steuerung der Faserstaubentwicklung faserverstärkter Kunststoffe beim mechanischen Recycling - Tölle, Lisa